2020
DOI: 10.1002/adem.202000451
|View full text |Cite
|
Sign up to set email alerts
|

Sandwiched Graphene Clad Laminate: A Binder‐Free Flexible Printed Circuit Board for 5G Antenna Application

Abstract: Printed circuit board (PCB), as the basic mechanically supports of electronic devices, is widely used in circuit, radio frequency (RF), and other fields. [1,2] Copper is the most commonly used conductive material in the PCB structure due to its high electrical conductivity and matured manufacture techniques. [3] Despite the advantages, with the increasing demand of electronic products, metal waste is becoming a severe problem, as it can cause significant environment pollutions. [4-6] Metal materials also suffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…45). First, the GAF and the dielectric substrate (FR-4, Silica gel lm, Rogers 5880, PET) were combined by hot pressing to form GAF Printed Circuit Board (PCB) 29 . To adapt the laser engraving machine, the carving patch of the device dimensions output by the simulation software was calculated using LPKF CircuitPro PL 2.0.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…45). First, the GAF and the dielectric substrate (FR-4, Silica gel lm, Rogers 5880, PET) were combined by hot pressing to form GAF Printed Circuit Board (PCB) 29 . To adapt the laser engraving machine, the carving patch of the device dimensions output by the simulation software was calculated using LPKF CircuitPro PL 2.0.…”
Section: Methodsmentioning
confidence: 99%
“…However, the conducting graphene layer in these structures typically has limited thickness or low coductivity, which results in high surface resistance and poor device performance 22,23 . Recent breakthroughs in the reduction of graphene oxide 24 and exfoliation of pristine graphene 25 have demonstrated that graphene assembled structures can reach electrical conductivities of up to 10 5 S/m [26][27][28] , and that such techniques can be applied in WCE 29,30 . Such electrical conductivity, however, is still two orders of magnitude lower than that of metal-based materials.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a flexible high conductivity graphene assembled film (GAF) was applied to antenna design reported in our previous works. The GAF antennas exhibited comparable gain, radiation patterns, and return loss to commercial copper antennas [11][12][13]. On this basis, we further investigate the development of GAF millimeter wave large antenna array.…”
mentioning
confidence: 88%
“…30,31 Furthermore, the GAF has tremendous mechanical properties 32 and passed the 180 large-angle cyclic bending pressure test. 8,11,33 The results are shown in Table . 2. Compared with copper.…”
Section: Graphene Assemble Filmmentioning
confidence: 99%